Pengaruh Ukuran Perusahaan, Fee Audit dan Audit Tenure Terhadap Pemilihan Tipe KAP Pada Perusahan Sektor Keuangan yang Terdaftar Di BEI Periode Tahun 2021-2023 - Habibah Sapitri; Fera Sriyunianti; Rangga Putra Ananto (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to examine the effect of company size, audit fees, and audit tenure on the selection of KAP types. The data used in this study are secondary data obtained from the company's annual financial reports. This study focuses on companies engaged in the financial sector listed on the Indonesia Stock Exchange for the period 2021 to 2023. The sampling technique uses the purposive sampling method, where sampling uses several specific criteria. From the results of purposive sampling, 140 observation data were obtained from financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 - 2023. The analysis method used is logistic regression analysis using SPSS version 25. The results of the study indicate that company size has an influence on the selection of KAP types, audit fees have an influence on the selection of KAP types, and audit tenure has an influence on the selection of KAP types.